ChemInform Abstract: Simple and Stereocontrolled Preparation of Benzoylated Phenylalanine Using Friedel—Crafts Reaction in Trifluoromethanesulfonic Acid for Photoaffinity Labeling. Issue 6 (11th February 2014) - Murai, Yuta; Wang, Lei; Muto, Yasuyuki; Sakihama, Yasuko; Hashidoko, Yasuyuki; Hatanaka, Yasumaru; Hashimoto, Makoto
Abstract The stereocontrolled Friedel‐Crafts benzoylation of chiral phenylalanine derivatives is described.